Design 5g Wideband Fractal Antenna - Salleh, Jumsiye (Universiti Sains Malaysia, 2017)
Microstrip patch antenna is one of the designed antenna that able to miniaturization the antenna which has more efficient that conventional antenna nowadays. This is because the impact of evolution modern wireless communication system that is fifth generation, 5G network that needed the small and compact antenna. Microstrip Fractal geometry is the design that used to obtain a wide-band response that required to perform the wide-coverage for many application with high speed of the 5G network. In this project, the antenna was designed and simulated by using CST Microwave Studio. The objective is to design a fractal antenna for portable communication device nowadays, to perform a parametric study on of parameter in design the wideband fractal antenna, to fabricate a wideband fractal antenna for modern wireless communication and to analyze a wideband fractal antenna that suitable for 5G system communication nowadays. The iteration of the fractal antenna and the modification of design will improve the bandwidth. Moreover, the antenna was fabricated on FR-4 substrate and then tested. The measurement results for proposed of single Design II antenna provides better performances which operate at 9.57 GHz (closely to 10 GHz) with wider bandwidth is 7.03GHz (8.18-15.21 GHz), VSWR is 1.19 which can be integrated into many portable devices for the 5G system.